Dampak Sosial Ekonomi dan Budaya Pembangunan Bandara Dhoho terhadap Desa Penyangga: Studi Kasus di Desa Tiron dan Desa Banyakan, Kediri - Imam Fachruddin; Dyah Ayu Rahmawati; Ajie Hanif Muzaqi (Society, 2024)
Infrastructure development plays a pivotal role in transforming rural areas, particularly through large-scale projects such as airports. This study explores the socio-economic and cultural impacts of Dhoho Airport development in Kediri on buffer villages, focusing on Tiron and Banyakan. The primary objective is to understand how airport development influences economic opportunities, social structures, and cultural dynamics in these communities. Employing a qualitative case study design, this research collected data through in-depth interviews with community leaders, participatory observations of social interactions, and documentation from government and local institutions. The findings reveal significant economic transformations, including livelihood diversification from agriculture to trade and services, fostering the growth of MSMEs. Socially, the airport has contributed to declining cooperation, reflecting a shift toward individualistic values. Culturally, modernization has accelerated acculturation, altering traditional practices and values, particularly among younger generations. Moreover, there is a growing awareness of education and skill development as communities adapt to emerging economic opportunities. This study underscores the importance of inclusive development policies that balance economic growth with the preservation of cultural identity and social cohesion.